Measurement and Interpretation of Exercise Ventilatory Efficiency - Phillips, Devin B.; Collins, Sophie É.; Stickland, Michael K. (Frontiers in Physiology, 2020)
Cardiopulmonary exercise testing (CPET) is a method for evaluating pulmonary and cardiocirculatory abnormalities, dyspnea and exercise tolerance in healthy individuals and patients with chronic conditions. During exercise, ventilation (V̇E) increases in proportion to metabolic demand (i.e. carbon dioxide production (V̇CO2)) to maintain arterial blood gas and acid-base balance. The response of V̇E relative to V̇CO2 (V̇E/V̇CO2) is commonly termed ventilatory efficiency and is becoming a common physiological tool, in conjunction with other key variables such as operating lung volumes, to evaluate exercise responses in patients with chronic conditions. A growing body of research has shown that the V̇E/V̇CO2 response to exercise is elevated in conditions such as chronic heart failure (CHF), pulmonary hypertension (PH), interstitial lung disease and chronic obstructive pulmonary disease (COPD). Importantly, this potentiated V̇E/V̇CO2 response contributes to dyspnea and exercise intolerance. The clinical significance of ventilatory inefficiency is demonstrated by findings showing that the elevated V̇E/V̇CO2 response to exercise is an independent predictor of mortality in patients with CHF, PH and COPD. In this article, the underlying physiology, measurement, and interpretation of exercise ventilatory efficiency during CPET is reviewed. Additionally, exercise ventilatory efficiency in varying disease states is briefly discussed.